2023
DOI: 10.3389/fimmu.2023.1127572
|View full text |Cite
|
Sign up to set email alerts
|

LAMP3 expression in the liver is involved in T cell activation and adaptive immune regulation in hepatitis B virus infection

Abstract: BackgroundThe disease burden caused by chronic hepatitis B virus (HBV) infection is still heavy, and the current treatment scheme has not achieved a complete cure. Changes in natural and adaptive immunity usually accompany chronic HBV infection. As a marker expressed on dendritic cells (DCs), whether lysosome-associated membrane glycoprotein 3 (LAMP3) participates in chronic HBV infection deserves further analysis.MethodsWe retrieved chronic HBV infection transcriptional information from the Gene Expression Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Upregulation of DC-LAMP was associated with T cell activation and adaptive immune regulation. There was a close relationship between the expression of the DC-LAMP TGF-β gene [ 10 ], which is an important factor leading to the intensification of fibrosis processes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of DC-LAMP was associated with T cell activation and adaptive immune regulation. There was a close relationship between the expression of the DC-LAMP TGF-β gene [ 10 ], which is an important factor leading to the intensification of fibrosis processes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…DC-LAMP + DCs express multiple ligands to interact with receptors on T cells, possibly being the most active immune regulators of lymphocytes. A close relationship between T reg cell markers (i.e., transforming growth factor β, TGF-β) and DC-LAMP mRNA levels was shown [ 10 ]. Dendritic-cell-specific intercellular-adhesion-molecule-3-grabbing non-integrin (DC-SIGN or CD209) is a C-type lectin receptor that is selectively expressed on DCs and is considered to be another marker of their maturity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that DCs accumulate in the liver of patients with MAFLD and produce pro-inflammatory cytokines (such as IL-1, TNF-α, IL-12, and IL-18) that drive the recruitment and activation of other immune cells, such as macrophages, T cells, and neutrophils (Heier et al, 2017;Yang et al, 2021). Moreover, DCs also contribute to the activation and differentiation of regulatory T (Treg) cells, which play a critical role in suppressing immune responses and maintaining immune tolerance (Wang et al, 2023). Dysregulation of DC function in MAFLD may hinder the induction of Treg cells and promote inflammation and fibrosis.…”
Section: Dendritic Cellsmentioning
confidence: 99%